Iranian Women and the Islamic Revolution of 1979 - (:unkn) unknown (My University, 2020)
The Islamic Revolution of 1979 was a pivotal event that changed the fabric of Iranian society and the history of the entire Middle East. Despite their far-reaching influence during the revolution, women are often misrepresented as agentless victims at the hands of a fundamentalist Islamic movement that stripped them of the rights they had won under the Shahs. My research paper shows that Iranian women were active participants in the revolution, and that they were driven towards the allure of the Islamic Revolution due to the corruption and secularism of Shah Mohammed Reza Pahlavi, as well as his government’s damaging appropriation of the women’s movement. In the context of the Shah’s unpopular policies, such as the secular modernization of Iran’s government and economy, as well as various human rights abuses by the secret police (SAVAK), Iranian women considered Islam a favorable and more culturally authentic alternative. Upon close examination of the Islamic Revolution of 1979, it is clear that women played a substantial role, mobilizing themselves before and during the revolution in order to create a truly popular movement.